1994
DOI: 10.1007/bf01458818
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of a confined polymer in solution using the dissipative particle dynamics method

Abstract: The dynamics of a bead-and-spring polymer chain suspended in a sea of solvent particles are examined by dissipative particle dynamics (DPDJ simulations. The solvent is treated as a structured medium, comprised of particles subject to both solvent-solvent and solvent-polymer interactions and to stochastic Brownian forces. Thus hydrodynamic interactions among the beads of the polymer evolve naturally from the dynamics of the solvent particles. DPD simulations are about two orders of magnitude faster than compara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
74
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(75 citation statements)
references
References 3 publications
1
74
0
Order By: Relevance
“…Kong et al 33 studied the dynamics of a DPD polymer in solution between two walls (without shear). Wall particles were kept in a "frozen" state, so that they could not move relative to each other.…”
Section: Simulation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kong et al 33 studied the dynamics of a DPD polymer in solution between two walls (without shear). Wall particles were kept in a "frozen" state, so that they could not move relative to each other.…”
Section: Simulation Methodsmentioning
confidence: 99%
“…Later on, it was, among other things, applied to study systems containing polymers, surfactant, and lipids. [33][34][35][36][37][38][39] Malfreyt and Tildesley 40 used the DPD technique to simulate equilibrium properties of polymer brushes. Españ ol and Warren 41 showed that the DPD model corresponds to a Hamiltonian system.…”
Section: Introductionmentioning
confidence: 99%
“…It was later extended to polymers by introducing bead-andspring type particles. [3][4][5][6] Español and Warren 7 showed how the noise and friction terms in the DPD method should be chosen to satisfy the fluctuation-dissipation theorem. When this condition is satisfied the model corresponds to a Hamiltonian system.…”
Section: Introductionmentioning
confidence: 99%
“…Many applications of DPD method 75 or its variants in the simulations of complex fluids have been reported, e.g., sphere colloidal suspensions ( [15]; [16]; [17]; [18]; [19]; [20]), colloidal suspensions of spheres, rods, and disks [21], viscoelastic fluid [22], ferromagnetic colloidal suspension [23], magnetic colloidal dispersions [24], soft matter and polymeric applications [25], [26], lipid bilayer [27], flows of DNA suspensions [28], poly-80 mer chains [29], red blood cell modelling [30], [31]; this list is not meant to be exhaustive.…”
Section: Introductionmentioning
confidence: 99%